Essential Biomolecules in Food Webs - Ruess, Liliane; Müller-Navarra, Dörthe C. (Frontiers in Ecology and Evolution, 2019)
We here review the ecological role of essential nutritional biomolecules [fatty acids (FA), amino acids (AA), sterols, vitamins] in aquatic and terrestrial food webs, encompassing the forces behind their environmental distribution. Across ecosystems, mutualistic relationships frequently ensure exchanges of vitamins between producer and demander, especially between B12 and other B vitamins as well as the AA methionine. In contrast, FA, sterols and most AA are transferred up the food chain via classical predator-prey interactions, and therefore have good biomarker potential for trophic interactions. As biomass-flow depends on the absolute amounts of potential limiting resources, considering solely the relative share in the respective biochemical group may under- or overestimate the availability to consumers. Moreover, if not accounted for, “hidden” trophic channels, such as gut symbionts as well as metabolic conversion of precursor molecules, can hamper food web analyses. Fundamental differences exist between aquatic and terrestrial ecosystems: Vitamin B12 produced by ammonium oxidizing Archaea is essential to many aquatic algae, whereas terrestrial plants escaped this dependency by using B12 independent enzymes. Long-chain ω3 polyunsaturated FA (LC-ω3PUFA) in aquatic systems mainly originate from planktonic algae, while in terrestrial systems, belowground invertebrates can well be a source, also supporting aboveground biota. Interlinks from terrestrial to aquatic ecosystems are of a biochemically totally different nature than vice versa. While biomass rich in proteins and LC-ω3PUFA is transferred to land, e.g., by trophic relationships, the link from terrestrial to aquatic ecosystems provides recalcitrant plant carbon, mainly devoid of essential nutrients, fuelling detrital food chains. Recent global changes influence food webs via altered input and transfer of essential biomolecules, but separating the effects of nutrients, CO2, and warming is not trivial. Current evolutionary concepts (e.g., Black Queen, relaxed selection) considering the costs of metabolic production partly explain food web dynamics, especially for vitamins, whereas adaptations to potential oxidative stress seem to be more important for LC-PUFA. Overall, the provision with essential biomolecules is precious for both heterotrophs and auxotrophs. These nutritional valuable molecules often are kept unaltered in consumer metabolism, including their stable isotope composition, offering a great advantage for their use as trophic markers.